Laser orbital perturbations in Hamiltonian framework - El-Saftawy, M. I; Khalifa, Nabawia (International Journal of Advanced Astronomy, 2018)
The effect of laser photon pressure on the spacecraft’s orbit is modeled. The force model developed taking into consideration atmospheric beam attenuation. However, adaptive optics assumed fixed on the laser system in order to eliminate the effect of atmospheric turbulence. The force of a single laser pulse proved as a conservative force. Consequently, its potential obtained using Legender polynomial. Assuming a spherical Earth, the Hamiltonian of the problem developed in terms of Dalaunay elements up to the first zonal harmonic. Using different ground-based laser systems, the model applied to the satellite Ajisai of NORAD ID 16908 and the LEO debris ASTRO-F DEB of NORD ID 29054. The numerical results emphasized that laser pressure has an effect on the orbit and it is well agreed with the results of the Newtonian treatment of the problem.